2016
DOI: 10.1155/2016/5436458
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of Nanotechnology in Diagnosis and Treatment of Metastatic Breast Cancer? Promising Scenarios for the Near Future

Abstract: Metastatic breast cancer represents a diagnostic and therapeutic challenge due to tumor heterogeneity and to various physiological barriers that hinder drug delivery to the metastatic sites. To overcome these limitations, nanoformulated drugs have been developed and tested in preclinical studies, and few of them have been successfully translated into clinical practice. In particular, liposomal anthracyclines and nanoformulated albumin-bound paclitaxel have revealed an improved therapeutic index when compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Metastasis is a sequential process that allows cancer cells to move from the primary tumor site and grow elsewhere in the human body [5,24]. This is still the leading cause of death in patients with breast cancer [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is a sequential process that allows cancer cells to move from the primary tumor site and grow elsewhere in the human body [5,24]. This is still the leading cause of death in patients with breast cancer [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is a sequential process that allows cancer cells to move from the primary tumor site and grow elsewhere in the human body [5,24]. This is still the leading cause of death in patients with breast cancer [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have revealed that breast cancer is responsible for 6% of the total 7.5 million cancer mortalities worldwide [3,4]. Although numerous advanced diagnostic and therapeutic methods have been used in the treatment of breast cancer, but its metastasis is still the primary cause of death [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis is a sequential process that allows cancer cells to move from the primary tumor site and grow elsewhere in the human body [5,23]. This is still the leading cause of death in patients with breast cancer [24,25].…”
Section: Discussionmentioning
confidence: 99%